Lipophilic Caffeic and Ferulic Acid Derivatives Presenting Cytotoxicity against Human Breast Cancer Cells - Serafim, Teresa L. (2011)
In the present work, lipophilic caffeic and ferulic acid derivatives were synthesized, and their cytotoxicity on cultured breast cancer cells was compared. A total of six compounds were initially evaluated: caffeic acid (CA), hexyl caffeate (HC), caffeoylhexylamide (HCA), ferulic acid (FA), hexyl ferulate (HF), and feruloylhexylamide (HFA). Cell proliferation, cell cycle progression, and apoptotic signaling were investigated in three human breast cancer cell lines, including estrogen-sensitive (MCF-7) and insensitive (MDA-MB-231 and HS578T). Furthermore, direct mitochondrial effects of parent and modified compounds were investigated by using isolated liver mitochondria. The results indicated that although the parent compounds presented no cytotoxicity, the new compounds inhibited cell proliferation and induced cell cycle alterations and cell death, with a predominant effect on MCF-7 cells. Interestingly, cell cycle data indicates that effects on nontumor BJ fibroblasts were predominantly cytostatic and not cytotoxic. The parent compounds and derivatives also promoted direct alterations on hepatic mitochondrial bioenergetics, although the most unexpected and never before reported one was that FA induces the mitochondrial permeability transition. The results show that the new caffeic and ferulic acid lipophilic derivatives show increased cytotoxicity toward human breast cancer cell lines, although the magnitude and type of effects appear to be dependent on the cell type. Mitochondrial data had no direct correspondence with effects on intact cells suggesting that this organelle may not be a critical component of the cellular effects observed. The data provide a rational approach to the design of effective cytotoxic lipophilic hydroxycinnamic derivatives that in the future could be profitably applied for chemopreventive and/or chemotherapeutic purposes.